Plugging properties and profile control effects of crosslinked polyacrylamide microspheres. Issue 30 (22nd April 2016) - Wang, Bo; Lin, Meiqin; Guo, Jinru; Wang, Dianlin; Xu, Fengqiang; Li, Mingyuan
ABSTRACT: In this article, the morphology, particle size, and plugging properties of crosslinked polyacrylamide (CPAM) microspheres were investigated through optical microscopy, scanning electron microscopy (SEM), nuclear‐pore membrane filtration experiments, a micro‐visual model, sandpack experiments, parallel twin‐tube plugging, and oil displacement experiments. The results revealed that the primary particle sizes of the CPAM microspheres ranged from several hundreds of nanometers to 5 μm; however, after the microspheres were fully swelled in water, their sizes increased by approximately five times of their original sizes. As a CPAM microsphere dispersion system had good dispersibility and deformation capabilities, a 1.2 μm nuclear‐pore membrane as well as the deep part of a sandpack tube could be effectively plugged. Consequently, the flow diversion effect was achieved in the vertical and planar directions. When the CPAM microspheres migrated in porous media, they could displace residual oil on the pole wall and water flow channel to realize the synchronization of profile control and coordination and improve recovery efficiency. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43666. Abstract :